2014
DOI: 10.1016/j.jvs.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Platelet inhibition by adjunctive cilostazol suppresses the frequency of cerebral ischemic lesions after carotid artery stenting in patients with carotid artery stenosis

Abstract: Objective: Optimal platelet inhibition is an important therapeutic adjunct in patients with carotid artery stenosis undergoing carotid artery stenting (CAS). Clopidogrel resistance is associated with increased periprocedural thromboembolic complications from neurovascular stent placement procedures. The addition of cilostazol to dual antiplatelet therapy (DAT) has been reported to reduce platelet reactivity and to improve clinical outcomes after percutaneous coronary intervention. This study was undertaken to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Regarding major/minor bleeding, 3 of the studies 17,20,21 did not report any result and 2 studies 16,22 reported null bleeding events after CAS. Only one study 19 reported 7 bleedings overall (6 access site hematomas and 1 hemorrhage due to Regarding the revascularization rate post ISR, only 3 studies 18,19,22 reported a pooled rate of 33 endovascular treatments in 51 cases of ISR (65%) without stratifying the results according to antiplatelet treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding major/minor bleeding, 3 of the studies 17,20,21 did not report any result and 2 studies 16,22 reported null bleeding events after CAS. Only one study 19 reported 7 bleedings overall (6 access site hematomas and 1 hemorrhage due to Regarding the revascularization rate post ISR, only 3 studies 18,19,22 reported a pooled rate of 33 endovascular treatments in 51 cases of ISR (65%) without stratifying the results according to antiplatelet treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Despite aspirin administration for 5 consecutive days after acute ischemic stroke, 27% of patients with HAPR at the time of the aARU measurement had persistent HAPR at the time of the ARU‐5 measurement. Previous studies found that adding other antiplatelet therapies to aspirin therapy was associated with a decrease in the rate of antiplatelet resistance in antiplatelet therapy‐resistant patients and had beneficial effects on the risks of ischemic events; however, there were other studies with conflicting results . Given that the frequency of combination antiplatelet therapy was higher in patients with NAPR than in patients with HAPR at the time of the ARU‐5 measurement, patients with HAPR at the time of the acute platelet function test may be candidates for additional antiplatelet therapies.…”
Section: Discussionmentioning
confidence: 99%
“…21,22) Furthermore, a study indicated that additional administration of cilostazol in clopidogrelresistant patients reduced platelet aggregation, significantly decreasing the incidence of new ischemic lesions on DWIs after CAS. 23) In the present study, triple antiplatelet therapy was administered in the perioperative phase, which might have significantly inhibited thrombus formation even with the appearance of LDA after CAS, contributing to the absence of symptomatic lesions. However, platelet aggregation monitoring was not conducted, and the relationship between platelet aggregation and LDA formation should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 85%